2009
DOI: 10.1186/gb-2009-10-11-r127
|View full text |Cite
|
Sign up to set email alerts
|

Genomic transcriptional profiling identifies a candidate blood biomarker signature for the diagnosis of septicemic melioidosis

Abstract: A diagnostic signature for sepsis caused by Burkholderia pseudomallei infection was identified from transcriptional profiling of the blood of septicemia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
178
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 52 publications
5
178
1
Order By: Relevance
“…The greater distance of influenza virus samples from mock samples in the condition tree compared to RSV samples suggested that the transcriptional changes on hAECs were more prominent during influenza virus infection than during RSV infection. To measure the magnitude of the gene expression changes induced by each viral infection, we converted transcript abundance into MDTH, a representative score indicating the degree of transcriptional perturbation for a given sample compared to its control (35). MDTH values were higher in influenza virus-infected hAECs than in those infected with RSV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The greater distance of influenza virus samples from mock samples in the condition tree compared to RSV samples suggested that the transcriptional changes on hAECs were more prominent during influenza virus infection than during RSV infection. To measure the magnitude of the gene expression changes induced by each viral infection, we converted transcript abundance into MDTH, a representative score indicating the degree of transcriptional perturbation for a given sample compared to its control (35). MDTH values were higher in influenza virus-infected hAECs than in those infected with RSV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…False-negative molecular detection of B. pseudomallei has been attributed to lower concentrations of the organism in blood (Supaprom et al, 2007). Whilst more complex methods, such as genomic transcription profiling using microarray technology have shown greater promise, this technology is generally neither available nor feasible in regions where this disease is endemic (Pankla et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, genome array studies in the peripheral blood of patients with melioidosis suggest that T cell functions may be impaired, with underexpression of transcripts related to T cells and cytotoxic cells. In contrast, overexpression of transcripts corresponding to PMN functions including the abundance of immature neutrophils (e.g., DEFA1, DEFA3, FALL-39) and genes encoding neutrophil cell-surface markers (such as ITGAM [CD11b], FCGR1 [CD64], CD62L, and CSF3R) was observed in blood of patients with sepsis compared with uninfected control subjects (17). We believe that PMNs may have multiple cytokine or cell contact-mediated immune-regulatory interactions with other cells of the immune response during B. pseudomallei infection, but to date this has not been investigated.…”
mentioning
confidence: 99%